Exploring the Work-Life Balance Experience Of Academic Participants: A Phenomenological Inquiry - Sabuero, Jimmy B. (Future Science / FSH-PH Publications, 2025)
the academic workplace, balance is under attack today more than ever before. It delves into the personal and social lived experiences of the participant who are faculty and at the same time academic leader of a state university in Northern Mindanao. Advanced research investigates how participants in higher education navigate and negotiate the multiple roles within and outside of their academic careers-pure description 14-campus environment used a phenomenological research design, involved academic leaders as participants, and individual, in-depth interviewed 14 campus participants with experiences deemed meaningful to exploring struggles and experience behind. In addition, coping behaviors and leaders' leadership philosophies. The academic experiences of these participants express the very real cost of wearing many hats, little time for oneself and high chances of burning out. But they also deploy several strategies that shape work culture to lean in a more positive direction. These involved controlling timing, limits and encouraging a healthy-lead culture. The participants also felt that they are the focus in this study and include everybody in policy construction and would want more diverse representations and on the other hand would guarantee campus acceptance of this policy. This study also identified that decision-makers need to act on evidence, and policy needs room to guide as the situation changes. University leaders may use the findings of this study to draft policies that enhanced work-life balance and organizational effectiveness. The self-care and mission can enable academic volunteers to set a stage for learning that works, the researcher, the faculty, students, and the community. experiences.